Pedosedimentary development of part of a Late Quaternary loess-palaeosol sequence in northwest Argentina - Kemp, Rob A. (2004)
The field properties, magnetic susceptibility, particle size, calcium carbonate content, soil micromorphology and optical luminescence ages of the upper 6.1 m and lowermost 4.7 m of the 45 m loess-palaeosol sequence at El Lambedero in the Tafí del Valle region of Tucumán Province (Sierras Pampeanas, northwest Argentina) have been used to set up a partial stratigraphy and chronology, as well as a basic pedosedimentary model of loess accumulation, palaeosol development, reworking and erosion for the site. The minimum ages derived from the basal part of the section suggest that loess began to accumulate some time before 165 ka. A thick and well-developed pedocomplex in the upper profile is correlated with at least the latter part of marine isotope stage (MIS) 5, whereas the overlying palaeosol may be attributable to pedogenic activity during MIS 3. The absence of material younger than 33 ka close to the surface of this rounded spur landform is probably the result of either non-deposition or erosional stripping in response to climatic change, or episodic uplift in this seismically active region. © 2004 John Wiley and Sons, Ltd.